Pengembangan Topologi Jaringan Di SDI Umamapu - Quelarmo Memito Petrus Paen; Pingky Alfa Ray Leo Lede; Reynaldy Thimotius Abineno (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
SDI Umamapu currently uses a Telkom Internet Service Provider (ISP) internet connection with a bandwidth capacity of 50 Mbps, which is only used in the principal's office and laboratory and does not cover other SDI Umamapu educational areas and limits SDI Umamapu teachers and staff from carrying out related tasks. with the Internet network. Therefore, the aim of this research is to design an Internet network using Mikrotik to help teachers and staff work more efficiently and expand the coverage area of ​​the SDI Umamapu Internet network. Apart from that, the SDI Umamapu Online Computer-Based National Examination (UNBK) is facilitated by 30 computers/laptops connected to the Internet network and other clients. In conducting research, the author uses the Network Development Life Cycle (NDLC) methodology: analysis, design, simulation, implementation, management and monitoring to build an Internet network to solve research problems. Through this research the author can learn a little more about the concept of a hotspot network and its configuration which can provide the author with knowledge about the advantages and disadvantages of Mikrotik RouterOS as a hotspot server. When measured from the results of QoS (Quality of Service) analysis before implementation, the throughput was 36.238 kbit/s (Kbps), packet loss was 1.3%, average delay was 0.389072 seconds, and throughput was 1.5% after implementation. 161.657 kbit/s (kilobits per second), average latency 0.5157133 seconds, packet loss 36%. This means that the speed of Internet access at SDI Umamapu has decreased by up to 36% due to the increase in the area of ​​the Internet network. However, even though network performance has decreased, the newly created Internet network continues to function well and smoothly.